PWE-001 A randomised controlled trial of colonoscopic "scope guide" caecal intubation accuracy. (22nd June 2015) - Cruttenden-Wood, D; Zeidan, S; Foster, JD; Nash, GF
Abstract : Introduction: The scope-guide is seen by many as indispensable for managing loop resolution during colonoscopy. What is unknown is whether the scope-guide configuration can accurately predict if the caecum has been intubated. Method: 100 images of the scope-guide pattern, from consecutive colonoscopies, were compiled by an individual consultant endoscopist. None of the patients had colonic resections. Half of the photographs documented the scope guide pattern whilst in the caecum (confirmed by appendix orifice and ileocaecal valve) and the other half were taken in the right colon but not in caecum. Three assessors, with endoscopic experience, were blinded to the randomised anonymised images as asked to record if the image correlated to 'caecal' on 'non-caecal' intubation. Results: The correct allocation to 'caecum' or 'not caecum' was recorded in 54% of cases. The assessors were no better at recognising images taken in or not in the caecum (54:54). The sensitivity and specificity were 54.6% and 54.0% respectively. The PPV and NPV was 54.3% and 54.3% respectively. Conclusion: Although beneficial in loop resolution, the scope guide image in isolation cannot be relied on to predict caecal intubation. Disclosure of interest: None Declared.